Photography in dentistry: Part I (Basics) - Mirfazaelian A. Assistant professor; Siadat H. Assistant professor (Tehran University of Medical Sciences, 2006)
Dentistry has always benefited from photography as an adjunct tool in diagnosis treatment planning and presentations. The main reason for taking dental photographs is to provide documents and supplements for treatment. A photograph facilitates communication between dentists and laboratories. Quality control will become more important to dental practice in near future and photographs can be used by dentists as self-checking tools. Nowadays performing lectures or publications without presenting pictures is inconceivable. The camera system must be easy to use and accessories should be always available. Although a good variety of equipments are now available and can be used for close-up photography, the special requirements of dental clinical photography are not always provided by the manufacturers and dealers' recommendations are not always correct. This article tries to help the readers to find and use the most suitable equipments for their routine dental practice.